Optimization of Sharia Banking Regulations in Developing the Halal Cosmetic Industry in Indonesia - Akbar, Wahyu; Kurniawan, Rahmad; Dakhoir, Ahmad; Fahmi, Chairul (IAIN Manado, 2024)
This paper examines the role of Islamic banking in developing the Indonesian halal cosmetics industry. The method used includes a qualitative descriptive study through exploratory studies on optimizing the role of Islamic banks in the development of the halal cosmetic industry. The data source uses primary and secondary data through data collection techniques from interviews to literature study. Then, data collection also involves the author's opinion regarding the research issue data analysis, which consists of data reduction, data presentation, conclusions, and verification. Challenges and opportunities in the halal cosmetics industry continue to experience increasingly significant developments that affect the growth and development of the halal cosmetics industry. Therefore, the synergy between Islamic banking institutions, the government, and even related institutions is undoubtedly needed. This needs to be implemented by Islamic banks to optimize regulations and roles in the development of the halal cosmetic industry. First is regulation, followed by the process of preservation and standardization of halal products. Second, the synergy of Sharia institutions for halal industry players can be achieved by providing financing funds, mentoring, and education. Third, the synergy of Islamic banks with educational institutions through inclusive awareness of the halal cosmetic industry in educational institutions.